2014
DOI: 10.3389/fnagi.2014.00264
|View full text |Cite
|
Sign up to set email alerts
|

The effects of intracranial volume adjustment approaches on multiple regional MRI volumes in healthy aging and Alzheimer's disease

Abstract: In neurodegeneration research, normalization of regional volumes by intracranial volume (ICV) is important to estimate the extent of disease-driven atrophy. There is little agreement as to whether raw volumes, volume-to-ICV fractions or regional volumes from which the ICV factor has been regressed out should be used for volumetric brain imaging studies. Using multiple regional cortical and subcortical volumetric measures generated by Freesurfer (51 in total), the main aim of this study was to elucidate the imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
287
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 392 publications
(297 citation statements)
references
References 34 publications
9
287
0
1
Order By: Relevance
“…In the present study, greater global brain atrophy was significantly associated with older age, larger ICV, lower education and presence of the ApoE ε4 allele [45,52,53,54,55,56], while gender and the cohort used did not have any significant effect, as previously reported [54,55,57,58]. To the best of our knowledge, this is the only study investigating the influence of all these confounding factors on global brain atrophy in the same sample.…”
Section: Discussionmentioning
confidence: 94%
“…In the present study, greater global brain atrophy was significantly associated with older age, larger ICV, lower education and presence of the ApoE ε4 allele [45,52,53,54,55,56], while gender and the cohort used did not have any significant effect, as previously reported [54,55,57,58]. To the best of our knowledge, this is the only study investigating the influence of all these confounding factors on global brain atrophy in the same sample.…”
Section: Discussionmentioning
confidence: 94%
“…FreeSurfer software (http://surfer.nmr.mgh.harvard.edu) was utilised to extract MRI (1.5 T) measured hippocampal volume where an atlas-based approach was implemented and has been validated for use in subjects with a great deal of morphologic variability. Uncorrected hippocampal volume for head size was used as a previous study showed that the association between hippocampal volumes and cognition was not altered by intracranial volume normalization [29]. Peptide CSF measures were generated from aliquot samples collected at the same time [30] …”
Section: Biomarkersmentioning
confidence: 99%
“…The HF changes in volume were also seen in patients with cognitive impairment, including those with Alzheimer's disease [1,46]. Reduction in the HF volume was observed in heavy cannabis use, in epilepsy, mild cognitive decline, dementia, major depression, the aged, traumatic brain injury, posttraumatic stress disorder, chronic alcoholism, borderline and antisocial personality disorders, obsessive-compulsive disorder, herpes simplex encephalitis, Parkinson's and Huntington's disease, Down's and Turner's syndrome, cardiac arrest, and Cushing's disease [1,10,14,38,42].…”
Section: Discussionmentioning
confidence: 90%
“…Firstly, the MR equipment and the used imaging parameters differ among the institutions, for example the strength of the magnetic field, the pulse sequence and the slice thickness [5,16,24,27,34]. Secondly, the application of various methods for the HF delineation, either the manual tracing or the automatic segmentation, may influence the final result as well [30,36,46,47]. Thirdly, the brain size of the participants exerts substantial statistical influences on the HF volume values [4].…”
Section: Discussionmentioning
confidence: 99%